A synopsis of catalogs and checklists of harvestmen (Arachnida, Opiliones) - Kury, Adriano B. (Zootaxa, 2012)
An annotated synopsis is presented of the publications which offer species checklists and catalogs of the arachnid orderOpiliones. Catalogs and checklists are included if they cover both (1) a suprafamilial group and (2) a country, continentalor zoogeographical region. Standardized information is given on the number of species treated and the taxonomic and geo-graphic scope. A total of 100 catalog works (7 of which are online only) are listed. They record from 4 to 6125 species,and they are classified into 3 categories: (1) manuals, which contain diagnoses and keys, (2) catalogs, which contain no-menclatural acts and synonymic literature headings and (3) checklists, which contain only a species list. Finally, a synopsisof key systematic works for each area in each zoogeographical region is given, and a species count is provided for all zogeographical regions of the world.